2001
DOI: 10.3354/ame025151
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of dietary bacteria to metal accumulation in the slipper limpet

Abstract: Recent studies have shown that dietary ingestion can be an important source for metal accumulation in aquatic animals. Whether bacteria can contribute significantly to the overall metal accumulation in these animals remains little known. In this study, we used the kinetic modeling approach to examine the relative contribution of the aqueous phase, bacteria, and phytoplankton, as sources for Cd, Cr, and Zn accumulation by the slipper limpet Crepidula onyx, a suspension feeder that can capture bacteria efficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…This may be the reason for higher tolerance to Zn at 100 ppm. Bacteria are a potentially important source of metal accumulation in filter-feeding mollusk like limpets as ingestion of bacteria contributed up to 17% for Zn accumulation (Qiu et al 2001). Interestingly, about 29% of the isolates were resistant to 100 ppm of cadmium salt.…”
Section: Discussionmentioning
confidence: 99%
“…This may be the reason for higher tolerance to Zn at 100 ppm. Bacteria are a potentially important source of metal accumulation in filter-feeding mollusk like limpets as ingestion of bacteria contributed up to 17% for Zn accumulation (Qiu et al 2001). Interestingly, about 29% of the isolates were resistant to 100 ppm of cadmium salt.…”
Section: Discussionmentioning
confidence: 99%
“…Cubadda et al (2001) and Davies and Cliff (1999) suggested that the feeding habits are involved in the process. Qiu et al (2001) demonstrated using kinetic modeling that the uptake from dietary phase (especially bacteria) dominated metal accumulation in the slipper limpets (87% for Cd).…”
Section: Metal Concentrations Versus Sizementioning
confidence: 99%
“…selected food items are of the organism's natural diet (Qiu et al, 2001), because each item may present a specific AE. Usually, two feasible options can be adopted on the determination of AE from laboratory experiments: (i) to select a small number of species (Wang et al, 1999b;Wang and Rainbow, 2000;Rainbow and Wang, 2001) or (ii) to work with the 'in situ' food Luoma et al, 1998;Ke and Wang, 2002).…”
Section: Community Vs Single Species Approachmentioning
confidence: 99%
“…Manipulative experiments using radioisotopes are among the best methods to obtain these (Wang and Fisher, 1999), and there have been many studies determining assimilation efficiency (AE), influx and efflux rates 1 for Cd and other metals by organisms Wang and Fisher, 1999;Wang et al, 1999a,b;Qiu et al, 2001;Rainbow and Wang, 2001;Ke and Wang, 2002;Rainbow et al, 2003).…”
Section: Introductionmentioning
confidence: 99%